Living Value Education Bagi Anak Berbasis Al-qur’an - Musyfiq Amrullah (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
The conclusion of this dissertation is that Living Value Education for children is based on The Quran, namely the education of the values of life in the form of religious, nationalist, integrity, independence, tolerance, and mutual cooperation which are the actualization of the maqâshid al-Qur'an. namely personal benefit common benefit and benefit to build a community. These values must be taught to become personalities to students which are based on the child's psychological development, namely at the basic level, because in this level they have a high enough egocentricity and tend not to have the will to see many things from the perspective of others. This LVE is integrated through the intracurricular, co- curricular and extracurricular learning processes in educational institutions. The concept of LVE in the al-Qur'an for children is to make value education with the principle of not burdening giving light burdens (and instilling responsibility with the principle of gradual/gradual. Living Value Education for children is found as life value education that starts from the time the child is in the womb to the age of puberty. This is based on the terms of the Quran related to children, namely: 1. Walad shows the child who is born, whether there is a nasab connection or not and the term walad does not limit whether they are still small or already large; 2. Ibn (which means boy or bint is a girl. This term is taken from the root word banau (the plural form is abnâأ). The mention in Arabic, it is possible that a child is a building for their parents. Parents as figures to build it. Allah made the parents as the builders of the building to create independent offspring; 3. Tifl a newborn child, the word thiflu means a child who still needs guidance and nurture; 4. Gulam shows a child who is entering puberty. From these four terms, it can be concluded that children from birth to puberty need education and build them so that they are stable and independent. So the basic education degree is the right level to strengthen the basics of Living Value Education. This writing supports the opinion of al-Ghazâly and Abdullah Nâsih 'Ulwan about education starting from womb, Thomas Lickona about the necessity to instill moral values and character that can be taught in schools, even schools have the authority to train values, morals and character. This dissertation also supports the opinion of David Hume, about values that oppose the concept of Decrates' Rationality, which justifies values and morality based on reason alone. This dissertation also supports the opinion of Darwis Hude and Doni Koesoema about human potential which is not limited to intelligence, but there are several other intelligences that need to be developed in a balanced manner and evaluation of assessments is not only focused on cognitive ones.This dissertation also supports the opinions of Ibn Kathir, Muhamad Qutbh, Nasaruddin Umar, and Nur Arfiyah Febriani about gender, namely that a mother is allowed to have activities outside the home with several conditions. On the other hand, this dissertation is different from Thomas Aquinas' concept of value, which considers good and bad values not by his will but only tools of God's behavior, the concept of values and the concept of Living Value Education (LVE) Diana Tillman, Rani Anggraini Dewi, and ALIVE (Association For Living Value Education) International. They only limit Living Value Education to twelve values, namely: peace, appreciation, love, responsibility, happiness, cooperation, honesty, humility, tolerance, simplicity, freedom, and unity. This dissertation is also different from Thomas Lickona's opinion which limits moral values with respect and responsibility. This dissertation is also different from the opinion of al-Qurthuby and As-Suyuthy who refuse women to engage in public activities.The method used by the author in this study used a qualitative method, based on library research (library research) using a transcendental phenomonology approach. Meanwhile, the method of interpretation used is the thematic method (tafsir maudhu'i) both when analyzing problems and when using the verses of the Qur'an.